1988
DOI: 10.1103/physrevlett.60.2156
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and Conductivity of Silicon and Germanium Induced by Indentation

Abstract: We report the observation, by transmission electron microscopy, that single-crystal silicon and germanium are converted to an amorphous state at room temperature directly under both Vickers and Knoop indentations. The effect is seen for crystal orientations of [001], [Oil], and [111], and with applied loads between 0.1 and 0.5 N. We also observe that the materials become electrically conducting under load and that the process is reversible on subsequent unloading and reloading. Furthermore, the transformed pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(199 citation statements)
references
References 13 publications
15
181
3
Order By: Relevance
“…(a) DMC by removing a ductile metallized layer resulted from the large contact pressure in cutting region; (b) BMC by material fracture leaving subsurface damages, of which the subsurface damage is as deep as 5-10 µm due to crack propagations in machining of silicon indentation process of brittle materials. The measurement results revealed a substantial increase in the conductivity of the material below the indenter that can be plastically deformed, which supports the theory of transition to a metallic state [25,26].…”
Section: Ductile Nature and Plasticity Of Brittle Materialssupporting
confidence: 65%
“…(a) DMC by removing a ductile metallized layer resulted from the large contact pressure in cutting region; (b) BMC by material fracture leaving subsurface damages, of which the subsurface damage is as deep as 5-10 µm due to crack propagations in machining of silicon indentation process of brittle materials. The measurement results revealed a substantial increase in the conductivity of the material below the indenter that can be plastically deformed, which supports the theory of transition to a metallic state [25,26].…”
Section: Ductile Nature and Plasticity Of Brittle Materialssupporting
confidence: 65%
“…It consists of a heavy tangle of dislocations the density of which is so high that it is not possible to resolve individual dislocations. Clarke et al [ 14] have recently shown that room-temperature indentation of silicon results in a crystalline-to-amorphous transformation directly underneath the indenter. However, at the temperatures under investigation here, i.e.…”
Section: N1e Plastic Zonementioning
confidence: 99%
“…the material simply tears apart to accommodate the indenter. An alternative accommodation mode is the decrease in the atomic volume 8 of the material underneath the indenter through high pressure phase transformations [25] and/or crystalline-to-amorphous transitions [ 14].…”
Section: Temperature Dependence Of Accommodation Modesmentioning
confidence: 99%
“…7,9,10 Stressinduced CAT in Si has in fact been widely observed under various mechanical loading conditions, such as indentation, 6,[10][11][12][13][14][15] ball milling, 16,17 scratching 2,7 and bending. 18,19 Clarke et al 6 firstly reported straining-induced amorphous Si (a-Si) through indentation experiments. On the basis of the sharp drop in the electric resistance measured during the loading process, they speculated that a possible path for the CAT is the transition from an intermediated highpressure crystalline phase (β-tin) to a-Si upon rapid unloading.…”
Section: Introductionmentioning
confidence: 99%